2012
DOI: 10.1364/josaa.29.002074
|View full text |Cite
|
Sign up to set email alerts
|

Speckle contrast for superposed speckle patterns created by rotating the orientation of laser polarization

Abstract: For a rough diffuser that fully depolarizes a linearly polarized laser, the speckle contrast of a fully developed speckle image can be reduced from 1 to 0.5 by polarization diversity. This reduction is achieved by rotating an x-polarized laser to the y-polarized orientation to form four independent speckle patterns with equal intensities during the detector exposure time. For the case of arbitrary rotation of the polarization, we derived a generalized speckle contrast formula for the superposed speckle pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 14 publications
(16 reference statements)
0
18
0
Order By: Relevance
“…For wavelength diversity, the use of laser diode arrays or a broadband laser is usually required to reduce speckles [6]- [8]; this increases the cost and complexity of light sources. The use of polarization diversity to reduce speckles is generally limited because lasers have only two polarization states [9]. Angular diversity is one of the most effective techniques, and speckle reduction can be achieved by a diffractive optical element (DOE), diffuser, multimode fiber, light pipe, etc.…”
Section: Introductionmentioning
confidence: 99%
“…For wavelength diversity, the use of laser diode arrays or a broadband laser is usually required to reduce speckles [6]- [8]; this increases the cost and complexity of light sources. The use of polarization diversity to reduce speckles is generally limited because lasers have only two polarization states [9]. Angular diversity is one of the most effective techniques, and speckle reduction can be achieved by a diffractive optical element (DOE), diffuser, multimode fiber, light pipe, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the superposition of independent speckle patterns reduces the contrast of the superposed speckle pattern [16]. Manipulation of the contrast can also be achieved, if polarization diversity is introduced to the case of superposition of correlated speckle patterns [17]. Superposition of uncorrelated speckle patterns has been reported to be useful for polarization sensing through a scattering medium [18].…”
Section: Introductionmentioning
confidence: 99%
“…Speckle is a drawback of laser display for it can downgrade the image quality greatly. To solve this problem, numerous methods have been proposed, such as: using a deformable mirror 3 or a scanning mirror 4,5 to realize angle diversity; using a broad-area vertical-cavity surface-emitting laser 6 or random lasers 7 to realize wavelength diversity; using a staircase element 8 or a refractive steppers 9 to realize optical path difference; rotating independent speckle patterns 10 or a magneto-optical disk 11 to realize polarization diversity; using a light pipe 12 or a multimode optical fiber bundle 13 to realize time averaging and so on. J. I. Trisnadi firstly proposed the speckle reduction method using Hadamard phase diffuser 14,15 .…”
Section: Introductionmentioning
confidence: 99%